PKM Pemanfaatan Media Sosial (Instagram) dengan Youth Learning Community Model untuk Penguatan Iman dan Karakter Remaja di Kuasi Paroki St. Andreas Oesapa - David Amfotis; Emerensiana Ngaga; Natalia M R Mamulak; Yovinia Carmeneja Hoar Siki (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to enhance the faith literacy and digital literacy of youth through the utilization of Instagram with the Youth Learning Community (YLC) model. The activities included socialization, mentoring, creative content production, and digital community account management. Evaluation was carried out through pre- and post-activity questionnaires distributed to 30 youth participants, as well as monitoring during the mentoring process. The results showed that 87% of participants understood the YLC concept, 78% were active in Room Community activities, and 85% were able to use digital media positively by relating it to faith values. In addition, the number of followers increased from 450 to 1,027, indicating public interest in the content produced. These findings demonstrate that the YLC digital platform can strengthen faith, build character, and encourage youth participation in church life. The program recommends developing more diverse content, providing advanced training, and ensuring continuous support from the parish so that the digital community can be managed independently and sustainably.